2007
DOI: 10.1002/j.2168-9830.2007.tb00922.x
|View full text |Cite
|
Sign up to set email alerts
|

Promoting Advanced Writing Skills in an Upper‐Level Engineering Class

Abstract: This paper summarizes the design and evaluation of an instructional approach aimed at improving the writing skills of a group of undergraduate engineering students. We sought to determine whether student performance in difficult writing skills such as argumentation and synthesis could be improved by integrating a single writing exercise into an upper level engineering course. In designing the exercise, we relied heavily on recommendations for best practices from the learning science community, specifically tho… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
51
0
1

Year Published

2008
2008
2019
2019

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 77 publications
(60 citation statements)
references
References 10 publications
0
51
0
1
Order By: Relevance
“…Yalvac, et al also report a need to focus on "visual thinking" in writing, though some of the issues they uncovered in their study were different than those found here. 6 The second area where the students failed to meet expectations was in providing feedback on appropriate citations to outside resources. This appears to be a consequence of the word choice in the prompt regarding this on the feedback form.…”
Section: Discussionmentioning
confidence: 99%
“…Yalvac, et al also report a need to focus on "visual thinking" in writing, though some of the issues they uncovered in their study were different than those found here. 6 The second area where the students failed to meet expectations was in providing feedback on appropriate citations to outside resources. This appears to be a consequence of the word choice in the prompt regarding this on the feedback form.…”
Section: Discussionmentioning
confidence: 99%
“…For this purpose, numerous projects were set [6,9,12,13,18,25,26] An in-depth and longitudinal study conducted at an NSF funded Engineering Research Center showed that university faculty are persistent to change their teaching approaches no matter they had attended numerous professional development activities over couple years [11]. Faculty who reported dramatic changes in their teaching approaches were the ones who worked in collaboration with the learning scientists and systematically designed their own evidence based instruction in their own classrooms; collected data from their students with the help of the learning scientists, and published their educational design study results in journals or presented at educational conferences.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Furthermore, engineering faculty often reinforce an academic orientation; for example, some suggest making writing more meaningful for students by asking them to take on the "professional role" of a graduate student in a research laboratory. 3 In sum, few university programs place practitioner concerns with writing at the same level they place practitioner concerns with technical skills.…”
Section: Introductionmentioning
confidence: 99%